1999
DOI: 10.1002/(sici)1096-9918(199908)28:1<200::aid-sia607>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced formation of titanium silicides

Abstract: In this article, we report on the laser‐induced formation of both C49 and C54 TiSi2 films with fine grains using Q‐switched Nd : YAG laser irradiation from Ti/Si samples. The films formed were characterized with micro‐Raman spectroscopy, high‐resolution transmission electron microscopy, energy‐dispersive spectrometry and atomic force microscopy. The TiSi2 films synthesized are single‐phased and thin, with fine grains and a smooth film/substrate interface on the atomic scale. The process is likely to proceed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Chen et al 30 have also reported that the transformation temperature into C54-TiSi2 can be significantly reduced by pulsed laser annealing. Moreover, the technologically favorable C54-TiSi2 phase has been obtained directly after the laser annealing step 30,32,33 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al 30 have also reported that the transformation temperature into C54-TiSi2 can be significantly reduced by pulsed laser annealing. Moreover, the technologically favorable C54-TiSi2 phase has been obtained directly after the laser annealing step 30,32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser annealing has also been investigated and several important benefits have been demonstrated. First, due to its fast ramping rate and short anneal duration, nanosecond laser annealing (UV-NLA) has been found to enable the formation of smaller grains of C49-TiSi2 than RTA [30][31][32] , increasing the density of C54-TiSi2 nucleation sites. Chen et al 30 have also reported that the transformation temperature into C54-TiSi2 can be significantly reduced by pulsed laser annealing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Networked Control Systems; TCNS June 2020 558-567 Wang, D., see Wang, Y., TCNS June 2020 977-989 Wang, D., see Li, F., TCNS Sept. 20201523-1533 Wang, L., see Lin, X., TCNS June 2020 592-602 Wang, P., see Xiang, L., TCNS June 2020 807-817 Wang, P., Wen, G., Yu, X., Yu, W., and Lv, Y., Consensus Disturbance Rejection for Linear Multiagent Systems With Directed Switching Communication Topologies; TCNS March 2020 254-265 Wang, S., Taha, A.F., Gatsis, N., and Giacomoni, M.H., Receding Horizon Con-trol for Drinking Water Networks: The Case for Geometric Programming; TCNS Sept. 2020 1151-1163 Wang, W., see Lin, F., TCNS March 2020 53-63 Wang, X., see Chen, H., TCNS March 2020 189-200 Wang, Y., Zhao, M., Yang, W., Zhou, N., and Cassandras, C.G., Collision-Free Trajectory Design for 2-D Persistent Monitoring Using Second-Order Agents; TCNS June 2020 545-557 Wang, Y., Shan, M., and Wang, D., Motion Wang, Y., Zhang, W., and Yu, L., A Linear Active Disturbance Rejection Control Approach to Position Synchronization Control for Networked Interconnected Motion System; TCNS 1746-1756nous Distributed Power Control of Multimicrogrid Systems; TCNS 1960-1973Wei, G., see Ju, Y., TCNS Sept. 20201489-1499 Wei, Q., Pedarsani, R., and Coogan, S., Mixed Autonomy in Ride-Sharing Net-works; TCNS Dec. 1940Dec.…”
Section: Time Decision For Multi-input and Multi-outputmentioning
confidence: 99%